Mask-Wearing Behavior Among Individuals Newly Diagnosed With Type 2 Diabetes: Insights From Community Health Screenings During the COVID-19 Pandemic in Indonesia - Yokota, Fumihiko; Anai, Akane; Lazuardi, Lutfan; Majid, Nurholis; Wulandari, Hanifah; Nishikitani, Mariko; Kikuchi, Kimiyo; Sato, Yoko; Ikeda, Subaru; Ahmed, Ashir; Maruf, Rafiqul Islam; Nakashima, Naoki (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
The coronavirus disease 2019 (COVID-19) pandemic has had a severe impact on people with type 2 diabetes (T2D) and their health behaviors. This study investigated the associations between T2D status and mask- wearing behaviors in public settings during the first wave of COVID-19 among community residents in Yogyakarta, Indonesia. Outreach health checkups and self-report questionnaires were cross-sectionally conducted to measure mask- wearing behavior, T2D status, and sociodemographic characteristics. Chi- square tests and bivariate and multivariate logistic regression were performed for data analysis. Out of 254 participants, nearly one-fourth (24%) were newly diagnosed with T2D, while 15% reported that they had never been diagnosed with T2D before. Bivariate and multivariate logistic regression models had no statistically significant associations between mask-wearing behavior and T2D status. However, Chi-square test results showed significant differences (P=0.02) in percentages of inconsistent mask-wearing behavior among those who were newly diagnosed with T2D (19%), those who had known as T2D (8%), and those who had no T2D (7%). Early diagnostic services and awareness education for T2D are imperative to reduce the disease severity and mortality for future pandemics, particularly among undiagnosed individuals who are unaware of their T2D status.